1986
DOI: 10.1111/j.1348-0421.1986.tb00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy against Group B Streptococcal Infection in Neonatal Mice Delivered from Preimmunized Pregnants

Abstract: Neonatal mice delivered from mothers preimmunized with heated or formalinized whole cell vaccines of type Ia, Ia/c and III/c group B streptococci were infected with each type of bacteria, and then serum antibodies of mothers and neonates who survived the experiments were measured by enzyme-linked immunosorbent assay. The relationship between the protectivity in neonate mice and the antibody titers to the type specific polysaccharide antigens and the protein c antigen of their sera were examined.In the Ia-immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…An active maternal immunization model [23] was used to evaluate protection of the pups resulting from vaccine-elicited immune responses in the dams. Female mice (2–10 per arm) were dosed at weeks 0, 3, and 6 with either 10 µg (CP/dose) of monovalent conjugate or 5 µg of GBS6 (CP/serotype/dose) formulated in 100 µL of 1 g/L AlPO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…An active maternal immunization model [23] was used to evaluate protection of the pups resulting from vaccine-elicited immune responses in the dams. Female mice (2–10 per arm) were dosed at weeks 0, 3, and 6 with either 10 µg (CP/dose) of monovalent conjugate or 5 µg of GBS6 (CP/serotype/dose) formulated in 100 µL of 1 g/L AlPO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to purify the c proteins using various extraction methods suggest that both the a and the fl antigen exhibit heterogeneity in molecular size ranging from 10-20 kD to 130 kD or more (3,8,13). Studies have indicated that the c-protein antigens may interfere with the resistance to opsonization and killing of GBS (8), and in vivo studies have shown a protective effect of anti-c-protein antibodies when the animals were preimmunized (9) or passively protected by injection of hyperimmune rabbit antisera (3,6,8,11).…”
mentioning
confidence: 99%